Liposomal hydrogel formulation for transdermal delivery of pirfenidone. (2nd April 2016) - Jose, Anup; Mandapalli, Praveen Kumar; Venuganti, Venkata Vamsi Krishna
Abstract: Context : Pirfenidone (PFD) is an anti-fibrotic and anti-inflammatory agent indicated for the treatment of idiopathic pulmonary fibrosis (IPF). The current oral administration of PFD has several limitations including first pass metabolism and gastrointestinal irritation. Objective : The aim of this study is to investigate the feasibility of transdermal delivery of PFD using liposomal carrier system. Materials and methods : PFD-loaded liposomes were prepared using soy phosphatidylcholine (SPC) and sodium cholate (SC). Encapsulation efficiency (EE) of PFD in liposomes was optimized using different preparation techniques including thin film hydration (TFH) method, direct injection method (DIM) and drug encapsulation using freeze–thaw cycles. In vitro drug release study was performed using dialysis membrane method. The skin permeation studies were performed using excised porcine ear skin model in a Franz diffusion cell apparatus. Results and discussion : The average particle size and zeta-potential of liposomes were 191 ± 4.1 nm and −40.4 ± 4.5 mV, respectively. The liposomes prepared by TFH followed by 10 freeze–thaw cycles showed the greatest EE of 22.7 ± 0.63%. The optimized liposome formulation was incorporated in hydroxypropyl methyl cellulose (HPMC) hydrogel containing different permeation enhancers including oleic acid (OA), isopropyl myristate (IPM) and propylene glycol (PG). PFD-loaded liposomes incorporated in hydrogel containing OA and IPM showed the greatest flux of 10.9 ± 1.04 μg/cm 2 /h across skin, which was 5-fold greater compared with free PFD. The cumulative amount of PFD permeated was 344 ± 28.8 μg/cm 2 with a lag time of 2.3 ± 1.3 h. Conclusion : The hydrogel formulation containing PFD-loaded liposomes can be developed as a potential transdermal delivery system.